Kabsa - et egyptisk ritualkompleks - Hinge, Helle (Religionsvidenskabeligt Tidsskrift, 1997)
The starting point is a report on a specific case of female circumcision. Subsequently follows an account of the debate as to whether female circumcision is or is not "Islamic", the prevalence of female circumcision, and the kabsa ritual complex. The kabsa complex is associated with Egyptian circumcisions, weddings and births. In the article it is described how kabsa is caused by impurity, and how it is solved. Eventually, the differencies and similarities between the kabsa ritual complex and the Muslim tahara-system are outlined. The two systems are syncretistically associated in contemporary Egypt.